2018 22nd International Conference on System Theory, Control and Computing (ICSTCC) 2018
DOI: 10.1109/icstcc.2018.8540655
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and real-time optimisation of an industrial cooling-water network

Abstract: This work deals with the problem of distribution of cooling water in an evaporation process. The aim is to develop a Real-Time Optimisation (RTO) tool which improves the resource efficiency by supplying the optimal water distribution within a surface-condensers network for a given production demand. The approach includes experimental models and the automatic update of fouling factor. The problem is formulated and solved via nonlinear programming. Production constraints and concerns about the practical implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Note that both networks (spinbath processing and cooling-water distribution) are coupled, so their operation is coupled too. In previous works, we have addressed the optimal evaporation load allocation considering the demand of each product for a given cooling power [16], and the optimal cooling water distribution for a given evaporation load according to the available water at the sources [17]. Furthermore, we have also studied ways to efficiently formulate and solve the optimization of the whole coupled system in real time, i.e., the spinbath allocation and water distribution [18].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Note that both networks (spinbath processing and cooling-water distribution) are coupled, so their operation is coupled too. In previous works, we have addressed the optimal evaporation load allocation considering the demand of each product for a given cooling power [16], and the optimal cooling water distribution for a given evaporation load according to the available water at the sources [17]. Furthermore, we have also studied ways to efficiently formulate and solve the optimization of the whole coupled system in real time, i.e., the spinbath allocation and water distribution [18].…”
mentioning
confidence: 99%
“…The outlet water temperature of each SC (To ev ) is computed with the data-based model ( 14) developed in [17] according to the inlet water temperature (Tin ev ), the flow (F ev ) and the state of fouling (K f ev ) of the SCs, which can be estimated online.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plant surrogate models were developed to estimate the SSC in Kalliski et al (2019), which, after straightforward manipulations, is found to depend on EC and on the cooling capacity of the surface condenser C pow , as shown in (1). The cooling system performance is also modelled experimentally: the outlet cooling-water temperature of the condensers T out is estimated by a polynomial function up to degree 3 on the cooling-water flow F w and affine in its inlet temperature T in , as proposed in (Marcos et al, 2018):…”
mentioning
confidence: 99%
“…The water distribution among plants is done in parallel and, additionally, the exceeding water in Subnet 1 (F c ) can go to Subnet 2 but not backwards (see Figure 1b). Further details on the evaporation network can be found in Palacín et al (2018); Marcos et al (2018).…”
mentioning
confidence: 99%